2003
DOI: 10.3346/jkms.2003.18.5.686
|View full text |Cite
|
Sign up to set email alerts
|

Serum Hepatitis B Virus (HBV)DNA Levels at Different Stages of Clinical Course in Patients with Chronic HBV Infection in an Endemic Area

Abstract: The aims of this study were to investigate serum hepatitis B virus (HBV) DNA levels at different clinical stages in patients with chronic HBV infection, and to determine the serum HBV DNA level that discriminated HBeAg-negative chronic hepatitis B (CHB) cases from inactive HBsAg carriers. In all, 222 patients, encompassing 68 HBeAg-positive CHB patients (HBeAg-positive, ALT-elevation), 89 HBeAg-negative CHB patients (HBeAg-negative, ALT-elevation), and 65 inactive HBsAg carriers (HBeAg-negative, ALT-normal), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
9
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
4
9
1
Order By: Relevance
“…[6][7][8][9] However, the median HBV DNA level for the HBeAg-positive patients was statistically higher than the HBeAg-negative ones and similar trend was observed between the HBeAg-negative CHB patients and the inactive carriers (Table). Various studies on different populations of the world suggest that a lower cut-off value appears to be a better marker for differentiating HBeAg-negative CHB patients from the inactive carriers 6-9 as compared to NIH recommended value of 10 5 copies/mL.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…[6][7][8][9] However, the median HBV DNA level for the HBeAg-positive patients was statistically higher than the HBeAg-negative ones and similar trend was observed between the HBeAg-negative CHB patients and the inactive carriers (Table). Various studies on different populations of the world suggest that a lower cut-off value appears to be a better marker for differentiating HBeAg-negative CHB patients from the inactive carriers 6-9 as compared to NIH recommended value of 10 5 copies/mL.…”
Section: Discussionsupporting
confidence: 60%
“…However, according to a study by Chu et al, 6 NIH recommended value excluded 45.0% of HBeAg-negative CHB patients in their population. Similarly, Hoe et al, 7 observed while studying Korean population, that NIH value exclude 40.4% HBeAg-negative CHB patients and additionally, 20.0% of the inactive carriers were above this value. Evidently, HBV DNA levels in Indian HBsAgpositive population are lower in both the cases.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…From Bangladesh also, our group as well as our colleagues have reported similar experience in the recent past [9][10] . Two more recent studies have rather reported that high HBV DNA load is associated with less severe histologic liver disease [11][12] .…”
Section: Discussionmentioning
confidence: 99%
“…HBV DNA load in CHB patients may be influenced by host factors like immune response and alcohol consumption and viral factors like genotype and pre-core/ core promoter mutations 12 . CHB patients may have fluctuating HBV DNA level, which may also explain such observation.…”
Section: Discussionmentioning
confidence: 99%